Immunomodulation for Severe COVID-19 Pneumonia: The State of the Art - Zhang, Yinhua; Chen, Yuanyuan; Meng, Zhongji (Frontiers in Immunology, 2020)
COVID-19 is a worldwide pandemic caused by novel coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Severe cases of COVID-19 have accounted for 10-20% of all infections, leading to more than 500,000 deaths. Increasing evidences suggested that the inflammatory cytokine storm originated from anti-SARS-CoV-2 immune response play important role in the pathogenesis of critically ill patients with COVID-19, which leads to mixed antagonistic response syndrome (MARS). In the early stage of severe COVID-19, systemic inflammatory response syndrome will cause acute respiratory distress syndrome and multiple organ dysfunction syndrome, and even multiple organ failure. While in the late stage of severe disease, increasing production of anti-inflammatory cytokines drive the immune response to be dominated by compensatory anti-inflammatory response syndrome, which leads to immune exhaustion and susceptibility to secondary infections. Therefore, precise immunomodulation will be beneficious for patients with severe COVID-19, immunosuppressive or immune enhancement therapy will depend on the disease course and the immune status. This review summarizes the current understanding of the immunopathogenesis of severe COVID-19, especially the role of the inflammatory cytokine storm in disease progression. Immune indicators and immunotherapy strategies for severe COVID-19 are reviewed and the potential implications are discussed.